Purchasing Power Parity and Trade Imbalances: Implications and Impact on International Finance - Siti Nurlaili Oktafiani (CV. Lenggogeni Data Publishing, 2023)
Purchasing power parity (GDP) is an economic concept that relates currency exchange rates to the prices of goods and services in different countries. This concept has important implications in international trade and global finance. This article discusses the importance of purchasing power parity in maintaining the balance of trade between countries and its impact on international finance. In the context of international trade, purchasing power parity serves as an important measuring tool in assessing whether a currency has weakened or strengthened excessively against other currencies. Significant trade imbalances between countries can indicate a violation of purchasing power parity, which can lead to volatile exchange rate fluctuations and global economic instability. In this article, we also analyze the impact of trade imbalances on international finance. A sustainable trade imbalance can lead to a balance of payments deficit or surplus, which has an impact on the country's capital flows and foreign exchange reserves. These implications affect monetary policy, currency stability, and foreign investment in the countries involved. Title in Bahasa Indonesia: Paritas Daya Beli Dan Ketidakseimbangan Perdagangan: Implikasi Dan Dampak Pada Keuangan Internasional